Prediction and Optimization of Magnetic Properties of Laser Welded AISI 430 Stainless Steels - H. Mostaan; M. Rafiei (Archives of Metallurgy and Materials, 2018)
The AISI 430 stainless steel with ferritic structure is a low cost material for replacing austenitic stainless steel because of its higher yield strength, higher ductility and also better polarisation resistance in harsh environments. The applications of AISI 430 stainless steel are limited due to insignificant ductility and some undesirable changes of magnetic properties of its weld area with different microstructures. In this research, a study has been done to explore the effects of parameters of laser welding process, namely, welding speed, laser lamping current, and pulse duration, on the coercivity of laser welded AISI 430 stainless steel. Vibrating sample magnetometery has been used used to measure the values of magnetic properties. Observation of microstructural changes and also texture analysis were implemented in order to elucidate the change mechanism of magnetic properties in the welded sections. The results indicated that the laser welded samples undergo a considerable change in magnetic properties. These changes were attributed to the significant grain growth which these grains are ideally oriented in the easiest direction of magnetization and also formation of some non-magnetic phases. The main effects of the above-mentioned factors and the interaction effects with other factors were evaluated quantitatively. The analysis considered the effect of lamping current (175-200 A), pulse duration (10-20 ms) and travel speed (2-10 mm/min) on the coercivity of laser welded samples.